Impulsiveness and Cognitive Patterns. Understanding the Perfectionistic Responses in Spanish Competitive Junior Athletes - González-Hernández, Juan; Capilla Díaz, Concepción; Gómez-López, Manuel (Frontiers in Psychology, 2019)
High performance sport requires that the athlete maintain a constant intensity and control of their personal resources, as well as a balance between the regulation of them and their performance. In all likelihood, such requirements involve the influence of their beliefs on the tasks to be performed, to improve and the confidence in their own resources to perform in competition. Theoretical arguments provides new insights for our understanding of multidimensional perfectionism and their relationships with other variables as to with affective experiences. In this study, perfectionism was conceptualized as a stable personality disposition, whereas the impulsiveness components were conceptualized as representing psychological mechanisms (or processes) underlying the relationships between perfectionism and sport experiences. For all the above, this work aims to establish and show profiles of perfectionist beliefs and impulsive responses, according sportive modality and their relationships. Under non-randomized, predictive and cross-sectional design, those who practice more team sports are expected to point out more functional resources than those who practice combat sports or endurance sports. Present work studies, with a predictive and transversal methodology design, psychological response in a sample of 487 athletes (273 boys; 214 girls), who practice high performance sport in stages of technification. Self-reports to measure impulsiveness, perfectionism and competence self-perceptions were administered. Results indicated that athletes with functional responses of impulsivity and perfectionism predicted better indicators in the perceptions of their own competence. At the same time, athletes with more reflective thoughts, more careful planning, generally less sensitive to rewards and behaviors, are more self-regulated and planned (functional impulsivity), also showing more moderate relationships between the most dysfunctional perfectionist beliefs and the competency response. Athletes who describes striving for the best and focusing on future goals and performances benefit from their perfectionism; they are setting goals and then seeking them out committing yourself to pushing hard and self-improvement. Increasingly, it is relevant for coaches and athletes to understand how the processes of self-regulation (impulsivity) and self-knowledge (perfectionism) can be formed and trained to offer opportunities to build psychological resources that enhance high-performance mental abilities.